CODE CHOICE WITHIN INTERCULTURAL COMMUNICATION AMONG ETHNIC MINORITY IN BRUNEI - Chuchu, Fatimah; Noorashid, Najib (Universitas Pendidikan Indonesia, 2015)
The influences of globalisation and multilingualism have caused linguistic diversity and emergence of interesting and unique sociolinguistic phenomena, for instance, language contact in intercultural communication. As the study of intercultural communication has yet to be studied at large, this research takes the opportunity to embark on a descriptive study of code choice within intercultural communication, relating to the ethnic minorities in Brunei Darussalam. This investigation aims to identify these ethnicsâ€™ preferable code choice within intercultural communication, and their needs and motivations practising those codes in a shared multilingual setting. Involving empirical investigation, this study was conducted on 60 native Brunei ethnics in Mukim Ukong, Tutong District. Research found that study involving multilingual settings and intercultural communications are rather relatively complex sociolinguistic phenomena, where speakers would employ different dialects or languages at an episode of communication, but still mutually understood by each other. To some extent, some speakers also accommodate their speech styles or languages to ease communication process between parties. The hegemony of globalisation, local vernacular, speakersâ€™ background and setting are among others influenced the selection of their everyday code choice. Â